Science and culture for members only : the Amsterdam Zoo Artis in the nineteenth century - Mehos, Donna C. (Amsterdam University Press, 2006)
A study of the role of Amsterdam's Artis Zoo and the range of the cultural events it offered in the formation of the national and class identity in the nineteenth-century Netherlands.